The paradox of being : truth, identity, and images in Daoism - Andersen, Poul, 1944- (Harvard-Yenching Institute monograph series, 2019)
"Addresses the concept of truth in Chinese Daoist philosophy and ritual. Through wide-ranging research into Daoist ritual, both in history and as it survives in the present day, shows that the concept of true reality that informs this tradition posits being as a paradox anchored in the inexistent Way"--Provided by publisher.